Molecular Characterization of Sewage Bacteriophage and Their Efficiency in Treatment of Antibiotic Resistant Bacteria (Medico Legal Update, 2021)
Background: The increasing prevalence of multi-drug resistant of bacteria strains, has become a globalproblem and therefore alternative method to antibiotics must be found. Bacteriophages are considered analternative agent to control infection and contamination of the bacteria. Method: We used RAPD-PCRtechnique in present study, and used restriction endonuclease conformed presence unknown DNA fragments.Results: In this study, we described the isolation and character development of lytic bacteriophages capableof infecting bacteria specifically. Lytic bacteriophages, specific to Escherichia coli, Klebsiella pneumonia,Salmonella typhi, clinical strains, was first isolated from sewage. We have analyzed the DNA (RAPD)-PCR technique to produce unique and reproducible band from 21 different bacteriophages infecting E.coli,K. pneumonia, S. typhi . Used restriction endonuclease conformed presence unknown DNA fragments.Conclusion: Phages was capable of eliciting efficient lysis of studied bacteria, revealing its potential as anon-toxic sanitizer for controlling bacterial infection and contamination in both hospital and other publicenvironments.